Interaction Strength of Hanger and Horizontal Steel Reinforcement of Dapped End Beams - Abdul Kareem Q. Mohammad; Rafaa M. Abbas (Civil Engineering Journal, 2023)
The dapped end beam members have a special end with low depth at the support area, which results in a weak area against shear stresses. Classical structural analysis doesn’t capture the precise steel reinforcement interaction at the dapped zone area. The main objectives of this study are to investigate the strength of the dapped end area and to analyze stresses in the steel reinforcement to evaluate the shear failure mechanism at the re-entrant corner. The experimental tests conducted on RC beam samples, in addition to the numerical simulation of these samples by a finite element program, have been compared with a mathematical model. The experimental program highlighted the strains in the steel reinforcement in the dapped region to calculate the magnitude of the stresses in the steel reinforcement. In the experimental program, six dapped beams were fabricated with a length of 3 m, a width of 150 mm, and a depth of 300 mm. The notched end has a 150-mm depth and 150-mm height. These beams were loaded by a concentrated load near support to investigate the shear strength capacity. From the results for steel reinforcement strain, it is found that hanger and horizontal steel reinforcements interact to provide dapped end shear strength. The study proposes a new approach to computing shear strength capacity at the re-entrant corner by adding the contributions of the horizontal and hanger steel reinforcement using an appropriate proportion strain factor. This method revealed greater carrying capacity for the dapped end beam compared with other common structural methods. The results of the numerical analysis were done by the ABAQUS finite element program, showing the same behavior as the experimental work. This study proved the common contribution of hanger and horizontal re-entrant corner steel reinforcement and proposed a new formula to determine the updated nominal shear strength. Doi: 10.28991/CEJ-2023-09-12-015 Full Text: PDF